Deconvoluting cracking mechanisms in fusion processing of steel-copper multi-materials via Operando X-ray characterisation - Andaç Özsoy; William A. Hearn; Steve Gaudez; Rijuta Jeswani; Yunhui Chen; Alexander Rack; Zoltan Hegedüs; Nicola Casati; Roland E. Logé; Steven Van Petegem (Virtual and Physical Prototyping, 2025)
This study investigates various cracking mechanisms and their prevalence in fusion processing of steel-copper multi-materials using operando X-ray diffraction and imaging during laser powder-bed fusion (LPBF) of 316L-CuCrZr multi-material. During this investigation, three main types of cracking were identified: (i) solidification cracking, (ii) metal-induced embrittlement (MIE), and (iii) liquation cracking. All cracking types are closely related to phase formation during processing and stem from two underlying mechanisms. First, liquid–liquid phase separation (LLPS) and the monotectic reaction in the 316L-CuCrZr system cause two liquids with vastly different solidification ranges to form, leading to solidification cracking. Second, LLPS and the monotectic reaction uniformly distribute Cu-rich liquid between the Fe-rich dendrites, leading to MIE and/or liquation cracking. Conducted based on the insights gained from the operando characterisation, further experiments showed that cracking can be drastically reduced by avoiding phase separation. However, the complete elimination of cracking necessitates chemical alterations in the material feedstock, indicating that while process adjustments can mitigate cracking, they may fail to fully prevent it. These findings serve as a guideline for understanding the underlying causes of cracking in steel-copper multi-materials, how process optimisation can effectively mitigate cracking, and to what extent such adjustments in processing can achieve this outcome.